SELECTION ERGONOMICALLY-SIZED SCHOOL DESK AND CHAIR BASE ON PREDICTIVE MODELS - Wutthisrisatienkul, Thidarat; Puttapanom, Sutanit (Life Sciences and Environment Journal, 2017)
Improperly sized school desks and chairs have many detrimental effects on the spines of the students, leading to both short and long term pain. Hence, it is important to assess the desks and chairs for a proper fit. Comparing a student’s anthropometric data with the desk and chair dimensions is the best way to make such an evaluation. Because obtaining anthropometric data can be difficult and time consuming, this paper proposes a methodology to obtain an adequate approximation of the student’s anthropometric data with only measurements of the student’s height. Because most public schools in Thailand are required to choose school desks and chairs according to the Thai Industrial Standards (TIS) Institute recommendation and there are 6 sizes available, this paper, also presents how to ergonomically select from the available TIS sizes for a secondary school. The data sample consisted of anthropometric measurements from 20 students, and was used to create simple linear regression predictive equations. The heights of 650 students were transferred to anthropometric data by the predictive equations and the predicted anthropometric measurements then used to evaluate TIS school desk and chair sizes. The results reveal that a combination of sizes 3 and 4 are more appropriate for secondary schools than the combination of sizes 4 and 5 recommended by TIS Institute.